2020
DOI: 10.1101/2020.05.29.123869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic cerebellar network organization across the human menstrual cycle

Abstract: The cerebellum contains the vast majority of neurons in the brain and houses distinct functional networks that constitute at least two homotopic maps of the cerebrum. While the functional organization of the human cerebellum has been characterized, the influence of sex steroid hormones on intrinsic cerebellar network dynamics has yet to be established. Here, we investigated the extent to which endogenous fluctuations in estradiol and progesterone alter functional cerebellar networks at rest in a woman densely … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Previous work in a developmental cohort has shown males exhibit stronger inter-network connectivity, while females exhibit stronger intra-network connectivity (Satterthwaite et al, 2015). Extant literature also suggests hormonal modulation of functional connectivity (Dubol et al, 2020;Fitzgerald, Pritschet, Santander, Grafton, & Jacobs, 2020;Hjelmervik, Hausmann, Osnes, Westerhausen, & Specht, 2014;Pritschet et al, 2020;Weis, Hodgetts, et al, 2019). In terms of functional connectivity features that discriminate sex, two studies identified that connections within and between frontoparietal and default mode networks strongly contribute to the predictions (Weis, Patil, et al, 2019;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in a developmental cohort has shown males exhibit stronger inter-network connectivity, while females exhibit stronger intra-network connectivity (Satterthwaite et al, 2015). Extant literature also suggests hormonal modulation of functional connectivity (Dubol et al, 2020;Fitzgerald, Pritschet, Santander, Grafton, & Jacobs, 2020;Hjelmervik, Hausmann, Osnes, Westerhausen, & Specht, 2014;Pritschet et al, 2020;Weis, Hodgetts, et al, 2019). In terms of functional connectivity features that discriminate sex, two studies identified that connections within and between frontoparietal and default mode networks strongly contribute to the predictions (Weis, Patil, et al, 2019;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%